Black plaster composite fiber prepared by upward electrospinning. Issue 24 (19th February 2019) - Xu, Yulong; Li, Kaili; Liu, Yong; An, Yan; Xing, Changmin
ABSTRACT: Black plaster is a traditional Herbal medicine with a long history; it is usually used in paste form. In this study, a black plaster/poly(ethylene glycol) (PEG) composite fiber was prepared by a novel upward melt electrospinning method. Scanning electron microscopy results show that the black plaster composite fiber has good morphology and uniform diameter. Thermogravimetric analysis results indicate that the heating temperature in the electrospinning process does not damage the composition of the black plaster, and drug components are effectively retained in the black plaster. Drug dissolution results show that the dissolution of poorly water‐soluble Draconis Sanguis in both pure black plaster fibers and composite fibers are significantly higher than that in traditional bulk black plasters. When the PEG content in the composite fiber is 85 wt %, the drug dissolution amount of Draconis Sanguis in the black plaster composite fiber is the highest. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47662. Abstract :